1. (х + 5)² - (х - 4)(х + 4) + (х - 3)(х - 3)(х + 7) =
х² + 25 + 10х - (х² - 16) + (х² + 9 - 6х)(х + 7) =
х² + 25 + 10х - х² + 16 + х³ + 9х - 6х² + 7х² + 63 - 42х =
х³ + х² - 23х + 104
2. (2 + у)(у² - 2у + 4) - у(у - 2)(у + 2) =
8 + у³ - у(у² - 4) = 8 + у³ - у³ + 4у = 4у + 8
1. (х + 5)² - (х - 4)(х + 4) + (х - 3)(х - 3)(х + 7) =
х² + 25 + 10х - (х² - 16) + (х² + 9 - 6х)(х + 7) =
х² + 25 + 10х - х² + 16 + х³ + 9х - 6х² + 7х² + 63 - 42х =
х³ + х² - 23х + 104
2. (2 + у)(у² - 2у + 4) - у(у - 2)(у + 2) =
8 + у³ - у(у² - 4) = 8 + у³ - у³ + 4у = 4у + 8